2022
DOI: 10.5114/hpc.2021.112364
|View full text |Cite
|
Sign up to set email alerts
|

The Selection of Stress Coping Strategies by University Students Based on Prior Covid-19 Exposure

Abstract: Background. The present study examined factors influencing the choice of coping strategies in response to stress caused by the pandemic. The aim of the study was the analysis of the selection of coping strategies chosen by university students stratified based on whether they had previously contracted coronavirus disease . Material and methods.A variant of the COPE questionnaire was used to examine the choice of coping strategies among 876 students of Krasnoyarsk (Russia) during the lockdown. Fifteen coping str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…On the other hand, psychological techniques concentrate on feelings, including efficient approaches like looking for sustenance coming from individuals, soothing down, ducting, and participating in video games excessively, as well as fleeing to alleviate tension directly [56,57]. A previous study revealed that waiting on college trainees along with coping techniques will certainly proactively manage student tension together with issues as chances for self-development as well as self-growing [58,59].…”
Section: Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, psychological techniques concentrate on feelings, including efficient approaches like looking for sustenance coming from individuals, soothing down, ducting, and participating in video games excessively, as well as fleeing to alleviate tension directly [56,57]. A previous study revealed that waiting on college trainees along with coping techniques will certainly proactively manage student tension together with issues as chances for self-development as well as self-growing [58,59].…”
Section: Coping Strategiesmentioning
confidence: 99%
“…University students that embrace energetic coping techniques are more inspired to take a direct method and handle tension [57]. They will have reduced scholastic exhaustion experiences while sitting exams [64].…”
Section: Coping Strategiesmentioning
confidence: 99%
“…We found only two studies analyzing preferred coping strategies a year a er the pandemic's beginning (Kuvaeva & Strel'nikova, 2021;Shpakov et al, 2021), indicating a steady decline in interest in the topic.…”
Section: Coping Strategies One Year a Er The Start Of The Pandemic (S...mentioning
confidence: 85%
“…Comparison of students who had and did not have COVID-19 (Shpakov et al, 2021) showed signi cant di erences in their use of individual coping strategies: students who did not have COVID-19 more o en used acceptance strategies (5.8 ± 1.44 and 5.5 ± 1.44, respectively, p = 00.1) and planning strategy (6.5 ± 1.33 and 6.2 ± 1.36, respectively, p = 0.05). e strategy of turning to religion was more common among students who recovered from Covid (3.7 ± 1.81 among healthy students, 4.0 ± 1.91 among recovered patients, p = 0.05).Analysis of Data on Coping Strategies Obtained with Other Standardized Methods…”
Section: Analysis Of Data On Coping Strategies Obtained With Copementioning
confidence: 99%
See 1 more Smart Citation